Determination of the relationship between static and dynamic modulus of elasticity in beech wood - BİRİNCİ, Emre (Mobilya ve Ahsap Malzeme Arastirmalari Dergisi, 2023)
In this study, the relationship between the dynamic modulus of elasticity determined using the stress wave method, which is one of the non-destructive test methods, and the static modulus of elasticity determined according to the TS ISO 13061-2 (2021) standard was investigated. In this context, randomly selected beech (Fagus orientalis Lipsky) timbers of 12x13x110 cm3 in dimensions were used. The time of flight of the timber in the radial and longitudinal directions was determined by using a FAKOPP microsecond timer with an accuracy of 1 μs. Oven-dry densities of the beech timbers were determined according to the TS ISO 13061-2 (2021) standard. Firstly, stress wave velocity and then dynamic modulus of elasticity values were calculated with the obtained data. The beech timbers were then cut into 20x20x320 mm dimensions for the static modulus of elasticity tests. Static modulus of elasticity resistance tests of the specimens were carried out in a Shimadzu AGIC/20/50KN universal test machine according to the TS ISO 13061-4 (2021) standard. Linear regression analyses of static and dynamic modulus of elasticity results were performed. According to the results of the analyses, it was determined that there is a strong relationship between the static and dynamic modulus of elasticity.